HASIL BELAJAR AGAMA DAN KONTRIBUSINYA TERHADAP PERILAKU KEKERASAN SISWA - Salsabila, Miah; Rohmatillah, Amaliah Tahta (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2024)
The purpose of this study is to examine how religious learning outcomes affect violent behavior among students at SMP Karya Gedeg Mojokerto. Using a quantitative approach that employs a correlational method, data was collected through a questionnaire focused on violent behavior, in addition to students' religious learning outcomes sourced from their report cards. The study population consisted of all eighth grade students and a portion of ninth grade students, with a purposive sample of 30 students selected for analysis. The results of this study show that students' average religious learning outcomes fall into the high category, with a score of (91.07), while their average violent behavior is categorized as moderate with a score of (23.87). A significant positive correlation was identified between students' religious learning outcomes and violent behavior through the Pearson Product Moment correlation test, resulting in a value of r=0.362 and p=0.049. This suggests that as students achieve higher results in religious learning, there is a tendency for violent behavior to increase, although the correlation remains at a low level. This research shows that factors beyond religious learning outcomes play a role in shaping students' violent behavior. Contributing elements include external influences such as the social environment and parenting in the family. This study recommends improving religious education that focuses on the values of tolerance and conflict resolution, as well as encouraging collaboration between schools and parents to foster a supportive learning atmosphere. This research is expected to provide efforts to prevent violence in the school environment.